Farm gate profitability of organic and conventional farming systems in the tropics - Amritbir Riar; Eva Goldmann; David Bautze; Johanna Rüegg; Gurbir S. Bhullar; Noah Adamtey; Monika Schneider; Beate Huber; Laura Armengot (International Journal of Agricultural Sustainability)
Systematic studies on the economic competitiveness of organic farming systems compared to conventional farming systems are particularly lacking in tropical environments. In tropical regions, the evaluation of organic production systems typically concentrates on main cash crops earmarked for export markets. Consequently, crops grown in rotation or in association with these main crops have been largely overlooked, with their contribution to farm profitability is often considered negligible due to perceived challenges in securing premium organic prices. To address this knowledge gap, we conducted an analysis of twelve years of economic data from four long-term farming system comparison trials in tropical regions. Our objective was to delve into the economic competitiveness of both organic and conventional production systems at the system level, considering not only the main cash crops but also the associated and rotational crops. The outcomes of our analysis revealed that in three out of four systems, the gross margins of organic and conventional systems were comparable. In the fourth system, the gross margins of the organic system were 13.13% lower, equivalent to $169.8 per hectare per year compared to the conventional system. Furthermore, the contribution of crops grown in rotation with these main crops remains similar even when premium prices are not obtained. In instances where premium prices for non-cash crops are secured, their profitability can even surpass that of cash crops. Additionally, in the case of agroforestry, companion plantings serve as valuable additions for both dietary and income diversity. These findings suggest that the profitability of an agricultural system is not solely dependent on whether it is organic or conventional but is instead influenced by various system components. The emphasis should shift from a singular focus on main cash crops to a more comprehensive understanding that considers the entire spectrum of crops within a farming system.